Studie křížení VRT s konvenční tratí u Vranovic - Drcmánek, Roman (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Cílem práce bylo navrhnout křížení VRT Jižní Morava s konvenční tratí železniční vlečky Pohořelice – Vranovice. Dále vymodelovat křížení ve 3D, který bude sloužit jako příprava pro BIM. Začátek úseku řešené vlečky se nachází na okraji obce Vranovice a konec úseku u obce Přibice. Řešení je navrženo ve 2 variantách, které byly následně porovnány i s možností úplného zrušení provozu na železniční vlečce.

The aim of the work was to design a crossing of the VRT South Moravia with the conventional line of the railway siding Pohořelice - Vranovice. Furthermore, to model the crossing in 3D, which serves as a preparation for BIM. The beginning of the section of the designed siding is located on the outskirts of the village of Vranovice and the end of the section near the village of Přibice. The solution is proposed in 2 variants, which were then compared with the possibility of complete cancellation of the railway siding.
Study of Fly-over Crossing High Speed Track with Conventional Line Near Vranovice
Keywords: Studie; VRT; železniční vlečka; křížení; porovnání; Documentation; HST; railway siding; crossing; comparison